ANALISIS SEMIOTIKA PESAN MORAL PADA FILM VINA SEBELUM 7 HARI - Fitri Sandawana; Andi Nurhabibi Marwil; Muhammad Idris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The film Vina Sebelum 7 Hari is based on a true story that portrays violence againts women, bullying, and legal injustice that still occur in Indonesia. This study aims to analyze the moral messages in the film using Roland Barthes’ semiotic approach, which divides meaning into three levels:denotation, connotation, and myth. This approach is applied to reveal how visual and verbal signs construct public understanding of social reality. The research method used is descriptive qualitative with a content analysis technique. Data were collected through direct observation of the film, recording significant scenes, and classifying meanings based on the categories of denotation, connotation, and myth. The analysis identified 13 data findings representing these three levels of meaning. The study reveals that Vina Sebelum 7 Hari is rich in symbolism reflecting social trauma, gender inequality, and societal belief in mystical elements. Symbolis such as hair, letters, spiritual dialogues, and wandering spirits convey complex meanings related to women’s resistance against injustice and an uneual social system. Moreover, several moral messages are identified, including friendship, self esteem, wisdom, and emphaty. These values offer social reality and humanity. Therefore, in the film functions not only as entertainment but also as a reflective and educational medium for society.